Rehabilitation of the edentulous mandible with implant-supported overdenture using ball attachments and healing abutments: A case report - Jun-Beom Park (Elsevier, 2009)
For many years, osseointegrated implant-supported overdentures have been used in the rehabilitation of the edentulous lower jaw with excellent results. In this report, additional implants with healing abutments were applied posterior to mental foramen on each side was used to achieve additional support to the overdenture. Keywords: Implant overdenture, Edentulous mandible, Ball attachment, Healing abutment